2022
DOI: 10.1186/s12884-022-05200-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the quality of antenatal care in a context of high utilisation: evidence from Telangana, India

Abstract: Background Antenatal care coverage has dramatically increased in many low-and middle-income settings, including in the state of Telangana, India. However, there is increasing evidence of shortfalls in the quality of care women receive during their pregnancies. This study aims to examine dimensions of antenatal care quality in Telangana, India using four primary and secondary data sources. Methods Data from two secondary statewide data sources (Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The country's northeastern, eastern, and southern parts had better birth-weight outcomes compared to other regions, which is consistent with the evidence from the fourth round of the NFHS in India [ 24 ]. Higher utilization and quality of ANC services, higher maternal literacy rates correlating with improved awareness, lower parity, and the varied sociocultural phenomenon could be attributed to this phenomenon [ 25 ]. Furthermore, in this study, having no health insurance increased the likelihood of having an LBW newborn, a finding akin to that in a study in Mexico although most health insurance in India does not cover outpatient expenses while regardless of insurance status, all government facilities are obliged to provide universal free-of-cost antenatal services to all beneficiaries [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The country's northeastern, eastern, and southern parts had better birth-weight outcomes compared to other regions, which is consistent with the evidence from the fourth round of the NFHS in India [ 24 ]. Higher utilization and quality of ANC services, higher maternal literacy rates correlating with improved awareness, lower parity, and the varied sociocultural phenomenon could be attributed to this phenomenon [ 25 ]. Furthermore, in this study, having no health insurance increased the likelihood of having an LBW newborn, a finding akin to that in a study in Mexico although most health insurance in India does not cover outpatient expenses while regardless of insurance status, all government facilities are obliged to provide universal free-of-cost antenatal services to all beneficiaries [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mIRA project took place in four predominantly rural districts in Bagmati Province, Nepal (Kavrepalanchok, Sindhupalchowk, Sindhuli and Dolakha) between April and December 2022. Twenty facilities-government Health Posts and Primary Health Care Centers and non-governmental Dhulikhel Hospital Outreach Centers-were selected to receive tablets with the EDSS software installed (20). Facilities were paired by type and reported ANC client volume for the previous year and then randomly allocated to receive either the mIRA or the WHO EDSS.…”
Section: Intervention and Settingmentioning
confidence: 99%
“…The implementation fidelity study used a mixed-method convergent design where quantitative and qualitative data were collected simultaneously (24). The intent was to offer a more complete understanding of implementation in all 19 facilities, drawing on quantitative and qualitative data from in-person monitoring visits, quantitative information captured in the backend data of the EDSS software, and repeat, unstructured observations and in-depth interviews conducted in four case study facilities (20).…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per our knowledge, in the Indian context there has been only one major nationwide study, utilising data from NFHS-4 that attempted to understand the adequacy of quality ANC, consisting each of necessary dimension [16] , which has been missing in other previous or subsequent studies [5,[17][18][19][20] . The present study is an extension to their efforts as it used the most recent data of NFHS-5, shown the trends and added some additional dimensions in looking up for determinants, which were lacking in the previous study.…”
Section: Introductionmentioning
confidence: 99%